2021
DOI: 10.22541/au.162610069.98503366/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate exerts stronger control on topsoil carbon persistence than plant input in alpine grasslands

Abstract: Chen et al. (2021) concluded that plant input governs topsoil carbon persistence in alpine grasslands. We demonstrated that the excluded direct effect of precipitation on topsoil Δ14C in their analysis was in fact significant and strong. Our results provide an alternative viewpoint on the drivers of soil carbon turnover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Thus, to consider these non‐linear relationships, we used log‐transformed plant variables in the subsequent SEM and partial correlation analysis. The comparison showed that if the non‐linear relationship was ignored, similar statistical results with Wu et al (2021) would be generated, that is, precipitation acted as the most important factor on topsoil Δ 14 C (Figure 1a). By contrast, if this non‐linear relationship was considered, the direct effect of climate on Δ 14 C would be removed during model optimisation, and our original result would be obtained, that is, plant input was more important than the climate in regulating the topsoil Δ 14 C (Figure 1b).…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…Thus, to consider these non‐linear relationships, we used log‐transformed plant variables in the subsequent SEM and partial correlation analysis. The comparison showed that if the non‐linear relationship was ignored, similar statistical results with Wu et al (2021) would be generated, that is, precipitation acted as the most important factor on topsoil Δ 14 C (Figure 1a). By contrast, if this non‐linear relationship was considered, the direct effect of climate on Δ 14 C would be removed during model optimisation, and our original result would be obtained, that is, plant input was more important than the climate in regulating the topsoil Δ 14 C (Figure 1b).…”
Section: Introductionsupporting
confidence: 75%
“…The real reason for the discrepancy between Wu et al ’s (2021) analysis and ours is that they did not consider the non‐linear relationship between plant C input variables and topsoil Δ 14 C, where logarithm transformation was only performed for mineral variables in their analysis. However, as depicted in Figure 1g in Chen et al (2021), the relationship between Δ 14 C and plant input was also non‐linear.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations